Curriculum change in Australia and Ireland: a comparative study of recent reforms - Gleeson, Jim; Klenowski, Valentina; Looney, Anne (Journal of curriculum studies, 2020)
Curriculum policies internationally are increasingly concerned with the promotion of national competitiveness and economic development. This involves more emphasis on skills than on knowledge, on learning than on teaching and on school/teacher autonomy than regulation from the centre. At the local level such global influences are inevitably refracted in a process known as glocalization. Using a critical policy historiography approach, this study explores globalization and glocalization forces in two relatively recent curriculum reforms-the Australian Curriculum and Ireland's Framework for Junior Cycle. Both reforms employ triadic models of curriculum design involving subjects/learning areas, key skills/general capabilities, statements of learning/cross-curriculum priorities. Globalization influences are clearly evident in the shared emphases in both jurisdictions on skills, learning and school/teacher agency. However, these reforms have inevitably been shaped by their respective local political and social contexts and the respective curriculum debates have been dominated by technical implementation issues such as curriculum overload in Australia and school-based versus external assessment in Ireland. Meanwhile, substantive issues such as the educational purposes of the reforms, the influence of market values and performativity and the significance of curriculum and teacher professionalism policymaking structures have been largely eschewed.